Students’ Perceptions of a Blended Course and its Effectiveness at a Mongolian University - Oyuntsetseg Namjildorj; Munkhtuya Buyandelger; Azzaya Tserendorj (Pascasarjana Universitas Negeri Makassar, 2023)
Blended learning has been considered one of the modern delivery modes of teaching and learning since the COVID-19 pandemic outreach. Although e-learning has been developing in most countries, its importance and needs were highly acknowledged by all educational organizations worldwide during COVID-19. All educational institutions worldwide run online or blended courses at some stage of their training. Regarding temporary demands such as the pandemic, learners had to study through online learning, and now it has become one of their regular learning modes. Meanwhile, educational institutions and their stakeholders were experiencing both online and blended programs and were provided opportunities to compare different delivery methods. Therefore, blended learning and teaching have become a more profitable way of teaching, especially in higher education. This article investigates the student’s perceptions of blended learning and its effectiveness based on the case of a Mongolian university. To achieve this goal, we conducted qualitative and quantitative research. The survey included 182 students from first-year to senior year to identify the challenges they faced, the experiences they gained, and their evaluation of the blended courses they enrolled in. The research questions were created on Google form, data was electronic via emails, and focused group interviews were conducted simultaneously. As a result of the survey, it has been revealed that there are several benefits and advantages to blended courses in the tertiary education sector of Mongolia. However, key factors such as the learning styles of Mongolian students, appropriate learning environment and course design, access to technology, and effective organization should be improved in the future in order to run the blended courses successfully.